Comparison of subjective and objective adherence measures for preexposure prophylaxis against HIV infection among serodiscordant couples in East Africa. (24th April 2016) - Musinguzi, Nicholas; Muganzi, Collins D.; Boum, Yap; Ronald, Allan; Marzinke, Mark A.; Hendrix, Craig W.; Celum, Connie; Baeten, Jared M.; Bangsberg, David R.; Haberer, Jessica E.
Abstract : Background: Preexposure prophylaxis (PrEP) efficacy is highly dependent on adherence. Yet, it is unclear which adherence measures perform best for PrEP. Methods: We compared three types of self-reported adherence questions (rating of ability to adhere, frequency of doses taken, percentage of doses taken) and three forms of objective adherence measurement [unannounced pill counts (UPC), electronic monitoring, plasma tenofovir levels] using data from an ancillary adherence study within a clinical trial of PrEP among East African serodiscordant couples (Partners PrEP Study). Monthly measures were assessed for the first 6 months of follow-up. Results: One thousand, one hundred and forty-seven participants contributed 6048 person-months of data to this analysis. Median adherence was high: self-reported rating (90%), self-reported frequency (93%), and self-reported percentage (97%); UPC (99%); and electronic monitoring (97%). Prevalence of steady-state daily dosing (SSDD; ≥40 ng/ml) was 74% in a random subset of tenofovir samples obtained from 365 participants. Discrimination of SSDD versus less than SSDD levels was poor for self-reported rating [area under the receiver–operating curve (AROC) 0.54], self-reported frequency (AROC 0.52), self-reported percentage (AROC 0.56) and UPC (AROC 0.58), but moderate for electronic monitoring (AROC 0.70). Correlation was moderate among self-reported measures, adherence (0.61–0.66), but low for these self-reported measures compared with UPC (0.32–0.36) and with electronic monitoring (0.22–0.28). Conclusion: Electronic monitoring was the only adherence measure with meaningful ability to discriminate between SSDD and less than SSDD plasma tenofovir levels. Correlation between subjective and objective measures was poor. Future research should explore novel approaches to adherence measurement as PrEP moves into demonstration projects and programmatic implementation.